2007
DOI: 10.1017/s0007114507280559
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of childhood overweight and obesity in China

Abstract: In order to investigate the determinants of childhood overweight and obesity in China, the prevalence of overweight (including obesity) was compared according to different dietary and physical activity patterns and parental body weight status. A total of 6826 children aged 7-17 years from the 2002 China National Nutrition and Health Survey were included in the study. Information for dietary intake was collected using three consecutive 24-h recalls by trained interviewers. The amounts of cooking oil and condime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 21 publications
7
69
1
5
Order By: Relevance
“…A similar report from Pakistan revealed that lack of physical activity was found to be significantly associated with overweight in adolescents [18]. Another study in China also indicated that regular physical activity was an important factor in reducing the prevalence of overweight and obesity [19]. The possible reason for this result might be due to lower energy expenditure caused by decreased vigorous/moderate physical exercise.…”
Section: Determinants Of Overweight/obesitymentioning
confidence: 93%
See 1 more Smart Citation
“…A similar report from Pakistan revealed that lack of physical activity was found to be significantly associated with overweight in adolescents [18]. Another study in China also indicated that regular physical activity was an important factor in reducing the prevalence of overweight and obesity [19]. The possible reason for this result might be due to lower energy expenditure caused by decreased vigorous/moderate physical exercise.…”
Section: Determinants Of Overweight/obesitymentioning
confidence: 93%
“…Adolescence, particularly teenagers age (13)(14)(15)(16)(17)(18)(19)) is a critical period for the development of overweight and obesity that transit into adulthood [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Sample design and study population For study sampling for the 2002 CNNHS, the method of multi-step cluster sampling was adopted (11) . Finally, 71 971 households were randomly selected to represent the national data.…”
Section: Methodsmentioning
confidence: 99%
“…A series of observational studies among Chinese population demonstrated significant association between intake of red meat and excessive body fat, measured as abdominal obesity, high BMI, and overweight (36)(37)(38) . A large cohort study of Japanese population (39) reported significant effect of red meat consumption on the development of type 2 diabetes.…”
Section: Association Of Meat and Milk Consumption With Cancer And Metmentioning
confidence: 99%